Supplementary Material from Humpback whale song complexity and evolution on a North-western Pacific breeding ground: Okinawa, Japan - Eleanor M. Marwood; Franca Eichenberger; Nozomi Kobayashi; Haruna Okabe; Sachie Ozawa; Luke Rendell; Ellen Garland (2025)
Supplementary methods, results, figures and tables.